Using AI to Enhance Listening Ability among English Freshman Students - Wiratno; Nurlia, Ratna; Mulhuda, M. Ali (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
Listening comprehension continues to present significant challenges for English freshman students, particularly due to limited exposure to authentic language input, rapid speech delivery, and the lack of interactive listening practice. This study investigated the effectiveness of Artificial Intelligence (AI), specifically ChatGPT, in enhancing students’ listening skills through the implementation of Classroom Action Research (CAR). The research involved 25 freshman students and was conducted in two cycles encompassing planning, action, observation, and reflection stages. Data were obtained from listening tests, classroom observations, questionnaires, and reflective evaluations. The findings revealed notable improvements in students’ listening comprehension, classroom participation, and learning motivation. The study concludes that ChatGPT has substantial potential to support listening instruction in higher education contexts.